Design and Performance Evaluation of an Arduino-Based Integrated Radiation and Environmental Monitoring System for X-Ray Laboratories - Ahmad Ramadhani; Felycia; Ratu Verlaili Erlindriyani; Nauval Franata; Muchtar Ali Setyo Yudono; Dina Estining Tyas Lufianawati (Department of Electrical Engineering, Faculty of Engineering, Universitas Lampung, 2026)
Continuous monitoring of radiation exposure and environmental conditions is essential to ensure safety and operational efficiency in X-ray laboratories. However, commercially available systems are often expensive and less adaptable to smaller facilities. This study proposes the design and performance evaluation of a low-cost, Arduino-based integrated monitoring device for X-ray laboratory conditions. The system integrates a Geiger–Müller detector for radiation counting with environmental sensors for temperature, humidity, and light intensity (DHT11 and BH1750). Experimental testing was conducted to evaluate the accuracy of the timer, sensor performance, and radiation counting capabilities using background radiation and a Cs-137 source. The results demonstrate that the system operates reliably, with deviations in timer counting below 1%, acceptable sensor accuracy, and consistent radiation count rates between detectors. The prototype is capable of real-time data display via a serial monitor and an OLED 1306 screen. This study demonstrates that the proposed system provides an affordable and effective solution for laboratory radiation and environmental monitoring.